2009
DOI: 10.3758/brm.41.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Using the World-Wide Web to obtain large-scale word norms: 190,212 ratings on a set of 2,654 German nouns

Abstract: This article presents a new database of 2,654 German nouns rated by a sample of 3,907 subjects on three psycholinguistic attributes: concreteness, valence, and arousal. As a new means of data collection in the field of psycholinguistic research, all ratings were obtained via the Internet, using a tailored Web application. Analysis of the obtained word norms showed good agreement with two existing norm sets. A cluster analysis revealed a plausible set of four classes of nouns: abstract concepts, aversive events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 28 publications
1
58
0
1
Order By: Relevance
“…The ratings from the undergraduate sample have become a standard reference in psycholinguistics, and they were used for comparison in Experiment 2 of the present study. Lahl, Göritz, Pietrowsky, and Rosenberg (2009) gathered ratings of German nouns via the Internet. Each noun heaviest of a set of 12 objects by using a scale a limited number of times.…”
Section: What Is Being Rated?mentioning
confidence: 99%
“…The ratings from the undergraduate sample have become a standard reference in psycholinguistics, and they were used for comparison in Experiment 2 of the present study. Lahl, Göritz, Pietrowsky, and Rosenberg (2009) gathered ratings of German nouns via the Internet. Each noun heaviest of a set of 12 objects by using a scale a limited number of times.…”
Section: What Is Being Rated?mentioning
confidence: 99%
“…Norms of affective properties of words have been published in multiple languages such as European Portuguese (Soares, Comesaña, Pinheiro, Simões, & Frade, 2012), Brazilian Portuguese (Kristensen, de Azevedo Gomes, Justo, & Vieira, 2011), French (Monnier & Syssau, 2013;Bonin, et al, 2003;Gilet, Grühn, Studer, and Labouvie-Vief, 2012, among others), German (Kanske & Kotz, 2010;Lahl, Göritz, Pietrowsky, & Rosenberg, 2009;Võ et al, 2009;Võ, Jacobs, & Conrad, 2006), Polish (Imbir, 2015), Finnish (Söderholm, Häyry, Laine, & Karrasch, 2013;Eilola & Havelka, 2010), Italian (Montefinese, Ambrosini, Fairfield, & Mammarella, 2014) and Dutch (Moors et al, 2013). In Spanish, the largest set of emotional norms so far was published in Redondo, Fraga, Padrón, & Comesaña (2007), which includes valence, arousal, and dominance norms for the Spanish translation equivalents of the original 1034 items from ANEW using a method very similar to that in Bradley & Lang (1999).…”
mentioning
confidence: 99%
“…Such rating studies have been reported for pictures (Lang, Bradley, & Cuthbert, 2008), sounds (Bradley & Lang, 1999b), and words in several languages, including English (Bradley & Lang, 1999a;Brown & Ure, 1969;Stevenson, Mikels, & James, 2007), Spanish (Redondo, Fraga, Padrón, & Comesaña, 2007), French (Bertels, Kolinski, & Morais, 2009;Bonin et al, 2003;Corson & Quistrebert, 2000;Messina, Moré, & Cantraine, 1989;Niedenthal et al, 2004;Syssau & Font, 2005 ), German (Grühn & Smith, 2008;Hager & Hasselhorn, 1994;Lahl, Göritz, Pietrowsky, & Rosenberg, 2009;Võ et al, 2009), and Finish (Eilola & Havelka, 2010). In Dutch, a study by Hermans and De Houwer (1994) provided valence ratings and subjective familiarity ratings for 740 Dutch words, of which 370 were adjectives referring to personality traits and 370 were nouns.…”
mentioning
confidence: 99%